Validasi Skor Skrining COVID-19 RSUP Dr. Sardjito Yogyakarta - Ulfa, Dinda; Sari, Djayanti; Kurniawati, Juni (Jurnal Komplikasi Anestesi, 2021)
Background: Dr. Sardjito’s hospital Covid-19 screening score is a tool to assess patients who are suspected of being infected using RT-PCR swab examination. Unfortunately, there has never been researched regarding the validity. Objective: Validating the Dr. Sardjito’s hospital Covid-19 screening score to assess patients suspected of Covid-19 infection which was confirmed by the results of the RT -PCR swab at the Dr. Sardjito Hospital Yogyakarta. Method: This study used an observational retrospective cohort design. Patients who were included in the inclusion criteria were those aged >18 years, from 24th April 2020 to 31th December 2020. Result: The number of study samples was 705 patients. Discrimination ability of Dr. Sardjito’s hospital Covid-19 screening scoring was assessed by AUC and the result was 0,556 (CI 95%: 0,51-0,61. Calibration ability obtained HL test value p=0.001 (p<0.05). Conclusion: Dr. Sardjito’s hospital Covid-19 screening scoring has a very weak discrimination ability and poor calibration, so the Dr. Sardjito’s hospital Covid-19 screening scoring is invalid in predicting the results of RT-PCR swab at Dr. Sardjito Hospital Yogyakarta.